A study on the proportion of hearing impairment among percussionists in Thrissur district of Kerala - A. T., Jubina Bency; ., Sarangi; Roy, Sebastian; Mathew, Shalu Sara; A., Shamseena; K., Smrithi; G., Unnikrishnan U. (International Journal of Research in Medical Sciences, 2021)
Background: Hearing loss is a cause of global concern. Percussionists are exposed to greater levels of continuous or intermittent noise than others. Little is known about the relationship between percussion activity and hearing impairment. The early detection of the same and subsequent management makes a significant reduction in the burden of health care services. The objective was to study the proportion of hearing impairment in percussionists in the district of Thrissur using an IOS based mobile application. Methods: A cross sectional study was done on percussionists from Thrissur district who has experience of more than five years and has no congenital or traumatic hearing loss. A predesigned semi structured questionnaire was given and hearing tests were done using a mobile application U hear in a sound proof setting to understand the current state of hearing ability amoung the percussionists. Results: A total of 39 subjects were involved in our study of which all were males. Mean age of our study population was 30.44+12.04. most of them were diagnosed with at least mild degree of hearing loss of one of the ear or both the ears. 15.4% of them had mild degree of hearing loss, 64.1% had moderate degree of hearing loss and 20.5% had severe hearing loss. Conclusions: The study shows percussionists are more exposed to sounds of various frequencies for longer duration, they are more prone to hearing loss. The study brought out that age is directly proportional to hearing loss, music induced hearing loss progress at a rate proportion to the work experience.